Significant relationships among frost tolerance and net photosynthetic rate, water use efficiency and dehydrin accumulation in cold-treated winter oilseed rapes - Urban, Milan Oldřich; Klíma, Miroslav; Vítámvás, Pavel; Vašek, Jakub; Hilgert-Delgado, Alois Albert; Kučera, Vratislav (Journal of plant physiology, 2013)
Five winter oilseed rape cultivars (Benefit, Californium, Cortes, Ladoga, Navajo) were subjected to 30 days of cold treatment (4 °C) to examine the effect of cold on acquired frost tolerance (FT), dehydrin (DHN) content, and photosynthesis-related parameters. The main aim of this study was to determine whether there are relationships between FT (expressed as LT50 values) and the other parameters measured in the cultivars. While the cultivar Benefit accumulated two types of DHNs (D45 and D35), the other cultivars accumulated three additional DHNs (D97, D47, and D37). The similar-sized DHNs (D45 and D47) were the most abundant; the others exhibited significantly lower accumulations. The highest correlations were detected between LT50 and DHN accumulation (r=-0.815), intrinsic water use efficiency (WUEi; r=-0.643), net photosynthetic rate (r=-0.628), stomatal conductance (r=0.511), and intracellular/intercellular CO2 concentration (r=0.505). Those cultivars that exhibited higher Pn rate in cold (and further a significant increase in WUEi) had higher levels of DHNs and also higher FT. No significant correlation was observed between LT50 and E, PRI, or NDVI. Overall, we have shown the selected physiological parameters to be able to distinguish different FT cultivars of winter oilseed rape.
Keywords: Photosynthesis; lethal temperature for 50% of plants; analýza hlavních komponent; FT; aklimatizace; frost tolerance; net photosynthetic rate; Frost tolerance; zmrazování; cvs; normalized difference vegetation index; cultivars; Pn; WUE; AP; Ci; Dehydrin; cultivar Benefit; Freezing; cultivar Navajo; Adaptation, Physiological; internal leaf CO(2) concentration; SDS–PAGE; abscisic acid; stomatal conductance; cold acclimation or cold acclimated; Cold acclimation; alkaline phosphatase; analýza rozptylu; NBT/BCIP; cultivar Ladoga; Analysis of Variance; Acclimatization; BEN; intrinsic water use efficiency (Pn/GS); sodium dodecyl sulphate polyacrylamide gel electrophoresis; dehydrin; principal component analysis; Principal Component Analysis; PCA; COR/LEA; photochemical reflectance index; water use efficiency (Pn/E); ABA; GS; E; roční období; DHN; CAL; rostlinné proteiny; CA; WUEi; Seasons; voda; transpiration; Brassica napus; Plant Proteins; cold regulated/late embryogenesis abundant; fyziologická adaptace; D47, D45, D37 and D35 stand for dehydrin accumulation according to their different molecular masses from protein gel blot analysis (∼97, ∼47, ∼45, ∼37 and ∼35 kD); LT(50); COR; NAV; Winter oilseed rape; LAD; Water; D97; cultivar Californium; cultivar Cortes; nitro-blue tetrazolium/5-bromo-4-chloro-3′-indolyphosphate; fotosyntéza; NDVI; PRI